The factors influencing street begging in Kota Kinabalu / Elvi Albert Watisin and Nurhidayah Syam Lahmuddin - Albert Watisin, Elvi; Lahmuddin, Nurhidayah Syam (2014)
Street beggars is a social phenomenon that mostly happened in countries believed to be poor and facing an unbalanced economic where some people are enjoying too much luxury but at the same time some are living under the level of poverty. However, there are other reasons that contribute to the issue of street beggars. Therefore, this research paper focuses on the factors that influence street beggars in Kota Kinabalu and obviously, it took place in Kota Kinabalu area such as Api-Api, Segama, and Sinsuran. This research paper also focuses on the impact of street beggars towards Kota Kinabalu. A set of 120 questionnaires were distributed in different target respondents such as in Kota Kinabalu City Hall, Enforcement Officer, Welfare Department officers and also the public. Structured interview also being conducted for the beggars that available in Kota Kinabalu area.